2013
DOI: 10.5047/gseku.e.2012.002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Joint Panel Shear Deformation in Beam-to-Column Connections Part 1: Results of the Experimental Test Program

Abstract: This research was performed to develop a deeper understanding in the effects of joint panel shear deformation on elasto-plastic behavior of the beam-to-column connections. Fourteen full-scale beam-to-column subassemblies were experimentally tested under cyclic loading and results are reported. Main parameters in this investigation were the joint panel strength ratio, weld joint detail, material toughness and column flange width to thickness ratio. It is shown that for each series of specimens with same failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In balanced and strong panel specimens, root of the weld access hole (SC) gives higher crack index compared to other hot spots and different weld joint details of S-type and F-type had no effect on cracking from this critical hot spot. Experimental test observations reported in part 1 of the paper 7) also confirmed the high potentiality of cracking at root of the weld access hole (SC) with no effect of weld joint detail. It was observed that in all specimens regardless of weld joint detail first crack initiation was occurred at root of weld access hole (SC) and the basic failure mode in all specimens was crack propagation from this hot spot.…”
Section: Crack Indexmentioning
confidence: 63%
See 4 more Smart Citations
“…In balanced and strong panel specimens, root of the weld access hole (SC) gives higher crack index compared to other hot spots and different weld joint details of S-type and F-type had no effect on cracking from this critical hot spot. Experimental test observations reported in part 1 of the paper 7) also confirmed the high potentiality of cracking at root of the weld access hole (SC) with no effect of weld joint detail. It was observed that in all specimens regardless of weld joint detail first crack initiation was occurred at root of weld access hole (SC) and the basic failure mode in all specimens was crack propagation from this hot spot.…”
Section: Crack Indexmentioning
confidence: 63%
“…In here, detail observations of failure of test specimens, reported in Part 1 of the paper 7) are newly discussed to show the detailed information of damages at hot spots. Table 1 presents the specification of specimens.…”
Section: Detail Observation Of Experimental Testsmentioning
confidence: 99%
See 3 more Smart Citations